NEK2 mediates ALDH1A1-dependent drug resistance in multiple myeloma - Yang, Ye (Oncotarget, 2014)
We reported previously that increased expression of aldehyde dehydrogenase 1 (ALDH1) in multiple myeloma (MM) is a marker of tumor-initiating cells (TICs) that is further associated with chromosomal instability (CIN). Here we demonstrate that member A1 of the ALDH1 family of proteins, ALDH1A1, is most abundantly expressed in myeloma. Enforced expression of ALDH1A1 in myeloma cells led to increased clonogenicity, tumor formation in mice, and resistance to myeloma drugs in vitro and in vivo. The mechanism underlying these phenotypes included the ALDH1A1-dependent activation of drug-efflux pump, ABCB1, and survival proteins, AKT and BCL2. Over expression of ALDH1A1 in myeloma cells led to increased mRNA and protein levels of NIMA-related kinase 2 (NEK2), whereas shRNA-mediated knock down of NEK2 decreased drug efflux pump activity and drug resistance. The activation of NEK2 in myeloma cells relied on the ALDH1A1-dependent generation of the retinoid X receptor α (RXRα) ligand, 9-cis retinoic acid (9CRA) – not the retinoic acid receptor α (RARα) ligand, all-trans retinoic acid (ATRA). These findings implicate the ALDH1A1-RXRα-NEK2 pathway in drug resistance and disease relapse in myeloma and suggest that specific inhibitors of ALDH1A1 are worthy of consideration for clinical development of new approaches to overcome drug resistance in myeloma.